2008
DOI: 10.1029/2008ja013086
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dependence and solar wind control of transpolar arc luminosity

Abstract: [1] The influence of the solar wind and the interplanetary magnetic field (IMF) on the luminosity of transpolar arcs (TPAs) is examined by taking into account seasonal effects. The study focuses on those transpolar arcs that appear after an IMF B y sign change during steady northward IMF. It includes 21 northern hemisphere events identified in a previous study from global UV images taken by the Polar spacecraft between 1996 and 2000. Sorting the TPA events by sign of the Earth dipole tilt we find that the TPAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Thus the flow direction is in agreement with the SuperDARN detection of a localized vortex. Kullen et al [2008] have recently shown that the plasma flows measured in the ionosphere are a good approximation for the global plasma convection in the magnetosphere, even in regions of strong, field‐aligned parallel E fields.…”
Section: Cluster Observations On 14 February 2001mentioning
confidence: 99%
“…Thus the flow direction is in agreement with the SuperDARN detection of a localized vortex. Kullen et al [2008] have recently shown that the plasma flows measured in the ionosphere are a good approximation for the global plasma convection in the magnetosphere, even in regions of strong, field‐aligned parallel E fields.…”
Section: Cluster Observations On 14 February 2001mentioning
confidence: 99%
“…The Cumnock (2005) study was expanded by Kullen et al (2008) who found that the brightness of theta aurorae which occur in the summer hemisphere after an IMF B y sign change during steady northward IMF shows the same dependence on season and solar wind conditions as the main auroral oval except in the nightside sector. Increasing TPA brightness is associated with high solar wind speed, strongly northward IMF, high IMF magnitude, and low solar wind density (which correspond to high solar wind Alfvén velocity).…”
Section: Polar Arcs During Northward Imfmentioning
confidence: 99%
“…In contrast to large-scale arcs, small-scale Sun-aligned arcs are seen about half the time during northward IMF (e.g., Lassen and Danielsen, 1978;Gussenhoven, 1982;Ismail and Meng, 1982). In a statistical study, Valladares et al (1994) examined stable narrow Sun-aligned optical polar cap arcs viewed by all-sky imaging photometers.…”
Section: Polar Arcs During Northward Imfmentioning
confidence: 99%
“…Kullen et al . [] reported a greater IMF B Y dependence on the formation of transpolar arcs in the summer months compared to winter but attributed this to lower arc luminosity in the winter months due to lower ionospheric conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that the solar wind dependence of polar ionosphere structure and dynamics varies with season. For our purposes, most notable is the seasonal variability of the IMF BY influence on the IMF B Y influence on the polar cap convection pattern [Papitashvili and Rich, 2002;Ruohoniemi and Greenwald, 2005], formation of transpolar arcs [Kullen et al, 2008], and field-aligned currents [Green et al, 2009]. Figure 14 shows the occurrence of F region TEC variations observed in the three months surrounding (a) winter and (b) summer solstice, during periods of dawnward (B Y < À2 nT) and duskward (B Y > 2 nT) IMF.…”
Section: 1002/2016ja022937mentioning
confidence: 99%